Targeting EZH2 in Cancer: Mechanisms, Pathways, and Therapeutic Potential - Maria Saveria Gilardini Montani; Rossella Benedetti; Mara Cirone (Molecules)
Enhancer of zeste homolog 2 (EZH2) is a methyltransferase involved in cell cycle regulation, cell differentiation, and cell death and plays a role in modulating the immune response. Although it mainly functions by catalyzing the tri-methylation of H3 histone on K27 (H3K27), to inhibit the transcription of target genes, EZH2 can directly methylate several transcription factors or form complexes with them, regulating their functions. EZH2 expression/activity is often dysregulated in cancer, contributing to carcinogenesis and immune escape, thereby representing an important target in anti-cancer therapy. This review summarizes some of the mechanisms through which EZH2 regulates the expression and function of tumor suppressor genes and oncogenic molecules such as STAT3, mutant p53, and c-Myc and how it modulates the anti-cancer immune response. The influence of posttranslational modifications on EZH2 activity and stability and the possible strategies leading to its inhibition are also reviewed.